Do Corruption Risk and Characteristics of the Top Management Team Matter for Company Performance? Evidence from Malaysia - Marzuki, Hafizah; Hasnan, Suhaily; Kharuddin, Khairul Ayuni Mohd; Ali, Mazurina Mohd; Saleh, Norman Mohd (Asian Academy of Management Journal of Accounting and Finance, 2025)
The purpose of this study is to empirically investigate the relationships between top management team (TMT) characteristics (including women representation, political connections, age and tenure) and company performance, moderated by corruption risk. The data analysis is conducted using financial information from publicly traded companies on the primary market of Bursa Malaysia for the period spanning from 2018 to 2022. The regression analysis reveals a significant association between the political connections and tenure of the TMT and company performance. In addition, the moderation analysis demonstrates that corruption risk has a significantly positive effect on the relationship between the representation of women in the TMT and political connections, as well ason company performance. From a theoretical aspect, this study adds to the governance literature on how corruption risk strengthens the relationship between TMT characteristics and company performance in Malaysia. From a practical aspect, the results of this study will aid Malaysian business leaders in understanding the importance of the role of women representation and political connections in TMT, while also helping them develop their corporate governance framework better in uncertain environments. Furthermore, this study offers a unique contribution by advising company owners to enhance the influence of the TMT in improving company performance in conditions of significant corruption risk.